Implementation and comparison of different taste masking techniques to design and assess dispersible tablet formulations - Alaa Elawni; Zuheir Osman; Mohammed Salih; Waleed Elballa; Mohammed Shayoub (Creative Pharma Assent, 2022)
The objective of this study was to assess the efficacy of several taste-masking techniques and to study the impact of different formulation variables on the physicochemical properties of dispersible tablets containing Ranitidine as a model drug. Ranitidine powder was taste masked using various techniques. Factorial design (24) was applied to design the set of tablet formulations. The four factors implemented were the manufacturing method, filler type, superdisintegrant type and superdisintegrant concentration. Levels selected were direct compression and wet granulation for the manufacturing method, microcrystalline cellulose and mannitol for the diluent type, sodium starch glycolate and croscarmellose sodium for superdisintegrant type, and 2% and 10% for superdisintegrant concentration. Granulation with calcium carbonate (ratio of 1:8) was the taste-masking method of choice to be implemented. The formulated tablets results revealed that the manufacturing method has a significant influence on all the tested physicochemical properties (p-values < 0.05) such as tablet’s weight variation, hardness, friability, and disintegration time. Croscarmellose sodium obtained better results than sodium starch glycolate. Both fillers obtained good properties when implementing direct compression method with croscarmellose sodium concentration of 2%, or wet granulation method with croscarmellose sodium concentration of 10%. Drug release was also increased by increasing concentration of croscarmellose sodium. These findings represent an easy manufacturing procedure with relatively low-cost materials that can be implemented to formulate dispersible tablets of bitter tasting drugs that will enhance patient compliance and lead to faster onset of action.